Discovery of the REN11 Locus From Vitis aestivalis for Stable Resistance to Grapevine Powdery Mildew in a Family Segregating for Several Unstable and Tissue-Specific Quantitative Resistance Loci - Karn, Avinash; Zou, Cheng; Brooks, Siraprapa; Fresnedo-Ramírez, Jonathan; Gabler, Franka; Sun, Qi; Ramming, David; Naegele, Rachel; Ledbetter, Craig; Cadle-Davidson, Lance (Frontiers in Plant Science, 2021)
Race-specific resistance loci, whether having qualitative or quantitative effects, present plant breeding challenges for phenotypic selection and for deciding which loci to select or stack with other resistance loci for improved durability. Previously, resistance to grapevine powdery mildew (GPM, caused by Erysiphe necator) was predicted to be conferred by at least three race-specific loci in the mapping family B37-28 × C56-11 segregating for GPM resistance from Vitis aestivalis. Here, nine years of vineyard GPM disease severity ratings plus greenhouse and laboratory assays were genetically mapped, using a rhAmpSeq core genome marker platform with 2000 local haplotype markers. A new qualitative resistance locus, named REN11, on chromosome (Chr) 15 was found to be effective in nearly all (11 of 12) vineyard environments on leaves, rachis, berries, and most of the time (7 of 12) on stems. REN11 was independently validated in a pseudotestcross with the grandparent source of resistance, ‘Tamiami’. Five other loci significantly predicted GPM severity on leaves in only one or two environments, which could support the hypothesis of race-specific resistance or their roles in different timepoints in epidemic progress. Loci on Chr 8 and 9 reproducibly predicted disease severity on stems but not on other tissues and had additive effects with REN11 on stems. The rhAmpSeq local haplotype sequences published here for REN11 and Chr 8 and 9 stem QTL can be directly used for marker-assisted selection or converted to SNP assays. In screening for REN11 in a diversity panel of 20,651 vines representing the diversity of Vitis, this rhAmpSeq haplotype had a false positive rate of 0.034% or less. The effects of the other foliar resistance loci detected here seem too unstable for genetic improvement regardless of quantitative effect size, whether due to race specificity or other environmental variables.